Neutrophil-Lymphocyte Ratio (NLR) and Lymphocyte-Monocyte Ratio (LMR) as Covid-19 Screening Parameters - Heny Syahrini; Trinugroho Heri Fadjari; Nadjwa Zamalek Dalimoenthe (Universitas Nahdlatul Ulama Surabaya, 2022)
Covid-19 diagnosis generally uses RT-PCR as the gold standard to detect coronavirus-2 (SARS-CoV-2); however, this method requires advanced laboratory equipment. Alternatively, Neutrophil-Lymphocyte Ratio (NLR) and Lymphocyte-Monocyte Ratio (LMR) can be used to identify viral infection. The study aimed: (1) to compare each NLR and LMR ratio in patients with and without COVID-19 and (2) to test the effectiveness of these ratios in identifying COVID-19. The study was conducted at the Haji Adam Malik Central General Hospital by acquiring 87 medical records data. The complete hematologic profile was analyzed from patients with and without COVID-19. The NLR and LMR ratio accuracy were analyzed as a screening tool for COVID-19. The AUC of NLR was 0.638, with cut-off ≤ 2.49, 47.6% sensitivity, and 80% specificity; therefore, the NLR accuracy as a screening for COVID-19 was defined as not good (just sufficient) because of AUC <0,7. The AUC of LMR was 0.661, with cut-off ≥ 3.23, 45.2% sensitivity, and 82.2% specificity; therefore, the LMR accuracy as a screening parameter for COVID-19 is defined as not good (just sufficient) because of AUC <0,7. There were significant differences in hematologic profile in neutrophil, lymphocyte, NLR, LMR between the patients in the COVID-19 group and non-COVID-19 group. NLR and LMR cannot be used as a screening tool because the Area Under Curve (AUC) is not good enough (just sufficient) in detecting COVID-19.